2008
DOI: 10.1103/physrevlett.101.120604
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Invariant Measure under Heat Flow

Abstract: We provide an explicit representation of the nonequilibrium invariant measure for a chain of harmonic oscillators with conservative noise in the presence of stationary heat flow. By first determining the covariance matrix, we are able to express the measure as the product of Gaussian distributions aligned along some collective modes that are spatially localized with power-law tails. Numerical studies show that such a representation applies also to a purely deterministic model, the quartic Fermi-Pasta-Ulam chai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 15 publications
(23 reference statements)
7
37
0
Order By: Relevance
“…On the other hand, numerical simulations of oscillator chains, including FPU chains, give various exponents [6,10,11,12,13] for different systems, often slightly higher than 1/3. This seems consistent with early results from mode-coupling theory (MCT), which predict a heat conductivity exponent of α = 2/5 [10,11,12], although recent MCT analyses predict exponents that depend on the leading nonlinearity [13,21] and the extent of transverse motion [12]. The apparent agreement between the numerical and MCT results has led to speculation that there may be two (or more) universality classes with different exponents [12,13].…”
Section: Pacs Numberssupporting
confidence: 75%
See 3 more Smart Citations
“…On the other hand, numerical simulations of oscillator chains, including FPU chains, give various exponents [6,10,11,12,13] for different systems, often slightly higher than 1/3. This seems consistent with early results from mode-coupling theory (MCT), which predict a heat conductivity exponent of α = 2/5 [10,11,12], although recent MCT analyses predict exponents that depend on the leading nonlinearity [13,21] and the extent of transverse motion [12]. The apparent agreement between the numerical and MCT results has led to speculation that there may be two (or more) universality classes with different exponents [12,13].…”
Section: Pacs Numberssupporting
confidence: 75%
“…The alternative, that α for the FPU-β chain will reverse its change with N and revert to ≈ 0.4, seems unlikely. Indeed, the latest MCT results [21] obtain α = 0.5 for even potentials (including the quartic model and the FPU-β model) which is quite far from earlier [13] and our numerical results. Nevertheless, it is unclear why the pure quartic system should need exceptionally large N. A final resolution of the issue requires an analytical demonstration of an error in one of the competing methods.…”
Section: Pacs Numbersmentioning
confidence: 45%
See 2 more Smart Citations
“…Recently, following a principal component analysis, we have numerically found that, in the basis identified by the eigenvectors of the covariance matrix, the nonequilibrium invariant measure of this model can be effectively expressed as the product of independent distributions aligned along collective modes that are spatially localized with power-law tails [20]. Moreover, several variables, such as the amplitudes of these modes, turn out to be Gaussian distributed.…”
Section: Introductionmentioning
confidence: 99%